The ATLAS experiment and its forward detector capabilities - Dova, María Teresa (2009)
The LHC will provide pp collisions at the unprecedented center-of-mass energy of 14 TeV. The proton beams will have an energy corresponding to 0.1 EeV in the rest frame of the target protons, approaching the region of the ultra-high energy cosmic rays where the lack of suitable accelerator data is the dominant source of systematic uncertainties in the analysis. The ATLAS experiment at the LHC is building detector systems to cover the forward region. The status of the ATLAS experiment and its forward detectors at the start-up of LHC is presented. The ATLAS forward physics program that will contribute to understand high energy hadronic interactions and help determine the primary cosmic ray composition is discussed.